FAKTOR – FAKTOR YANG MEMPENGARUHI PERMINTAAN WISATAWAN DOMESTIK TERHADAP OBJEK WISATA BAHARI PULAU CINGKUAK KABUPATEN PESISIR SELATAN - Agustin, Agustin; Sentosa, sri Ulfa; Aimon, hasdi (Jurnal Kajian Ekonomi, 2014)
This study aimed to analyze factors - factors that affect the demand fordomestic travelers to the island marine attraction Cingkuak. The data used areprimary data with a sample size of 133 people. The study used multiple linearregression method using the OLS approach (Ordinary Least Square). ), Which isassumed to be constant tourist attraction means based on observations did notchange from observation to observation. The study concluded that 1) the joint -the same travel expenses, income travelers, travel motivation, ease of visiting nosignificant effect on the demand for domestic travelers to the island marineattraction Cingkuak. While the number of family members, security and comfortof a significant effect on demand for domestic travelers to the island marineattraction Cingkuak. 2) the partial cost of the trip, travelers income, number offamily members, travel motivation significant effect on the demand for domestictravelers to the island Cingkuak marine attractions, while visiting the ease, safetyand comfort no significant effect on the demand for domestic travelers to theisland marine attraction CingkuakKeywords : Demand, domestic tourists, marine tourism